Gambaran Tingkat Stres pada Penderita Diabetes Melitus di Prolanis Puskesmas Purwokerto Timur II - Handayani, Titi Sayekti; Anam, Akhyarul; Taufik, Agis (Journal of Bionursing, 2025)
Background: Diabetes mellitus is a long-term chronic disease that requires regular blood sugar control and lifelong treatment. Stress can very easily occur in diabetes mellitus sufferers due to the disease they are experiencing. This study aims to determine the level of stress in diabetes mellitus sufferers. Method: Descriptive research with a cross sectional method involving 52 respondents and using simple random sampling techniques. Data was obtained using the Diabetes Distress Scale (DDS)-17 questionnaire which was filled in through a distributed questionnaire and processed using univariate analysis. Results: The majority of respondents were women, had at least elementary school education and were responsible for health financing independently, had suffered for ≥5 years, and were sufferers with complications, HbA1C level ≥7%, and mean age 61.94 years. The majority of diabetes mellitus sufferers who took prolanis experienced moderate levels of stress. Conclusion: Most respondents had a moderate level of stress with the emotional burden domain being higher than other domains. Efforts to reduce the stress experienced by diabetes mellitus sufferers need to be made.